Perioperative critical care management for patients with aneurysmal subarachnoid hemorrhage - Lee, Kiwon (The Korean Society of Anesthesiologists, 2014)
Despite significant regional and risk factor-related variations, the overall mortality rate in patients suffering from aneurysmal subarachnoid hemorrhage (SAH) remains high. Compared to ischemic stroke, which is typically irreversible, hemorrhagic stroke tends to carry a higher mortality, but patients who do survive have less disability. Technologies to monitor and treat complications of SAH have advanced considerably in recent years, but good long-term functional outcome still depends on prompt diagnosis, early aggressive management, and avoidance of premature withdrawal of support. Endovascular procedures and open craniotomy to secure a ruptured aneurysm represent some of the numerous critical steps required to achieve the best possible result. In this review, we have attempted to provide a contemporary, evidence-based outline of the perioperative critical care management of patients with SAH. This is a challenging and potentially fatal disease with a wide spectrum of severity and complications and an often protracted course. The dynamic nature of this illness, especially in its most severe forms, requires considerable flexibility in clinician management, especially given the panoply of available treatment modalities. Judicious hemodynamic monitoring and adaptive therapy are essential to respond to the fluctuating nature of cerebral vasospasm and the varying oxygen demands of the injured brain that may readily induce acute or delayed cerebral ischemia.